The impact of COVID-19 related lockdown measures on self-reported psychopathology and health-related quality of life in German adolescents - Koenig, Julian; Kohls, Elisabeth; Moessner, Markus; Lustig, Sophia; Bauer, Stephanie; Becker, Katja; Thomasius, Rainer; Eschenbeck, Heike; Diestelkamp, Silke; Gillé, Vera; Hiery, Alisa; Rummel-Kluge, Christine; et al. (European child & adolescent psychiatry, 2023)
The impact of school-closings on adolescents’ mental health and well-being in the management of the ongoing COVID-19 pandemic is subject to ongoing public debate. Reliable data to inform a balanced discussion are limited. Drawing on a large ongoing multi-site project in Germany, we assessed differences in self-reported psychopathology in a matched conveniencesample of adolescents assessed pre- (November 26, 2018 to March 13, 2020; n = 324) and post the first lockdown (March 18, 2020 to August 29, 2020; n = 324) early 2020 in Germany. We found no evidence for an increase in emotional and behavioral problems, depression, thoughts of suicide or suicide attempts, eating disorder symptoms, or a decrease in general health-related quality of life. Reported suicide plans significantly decreased from 6.14 to 2.16%. Similarly, conduct problems decreased in the post-lockdown period. Family risk-factors did not moderate these findings. The influence of socioeconomic status on emotional and behavioral problems as well as depression decreased during the lockdown. Based on the present findings, the first school-closing in Germany had no immediate and severe impact on adolescents’ well-being. However, caution is warranted as our data covers a fairly small, affluent sample over a limited time-span and long-term consequences cannot be ruled out.
Online veröffentlicht: 10 July 2021
Gesehen am 23.10.2023